Metafory w słuŜbie budowania toŜsamości. Krytyczna Analiza Dyskursu jako narzędzie badania dyskursu katolickiego na temat mniejszości homoseksualnej i zwolenników teorii gender (na przykładzie medialnych wypowiedzi Dariusza Oko - Kościańczuk, Marcela (Studia Edukacyjne, 2020)
The article presents an analysis of Dariusz Oko’s articles about the homosexual minority and people who are gender studies’ scholars or supporters. It shows metaphors and comparisons as tools of creating identity and ideological discourse. Narration is analyzed according to Critical Discourse Analysis tools. I present the re-scalation mechanism and compare Dariusz Oko’s rhetorical tools against envious prejudice.